(untitled) (Research, Society and Development, 2022)
In late December 2019, an outbreak of an emerging disease (Covid-19) due to a novel coronavirus (called SARS-CoV-2) quickly turned into a pandemic. The reassessment of drugs for use as antiviral treatments was one of the first therapeutic initiatives, especially chloroquine/hydroxychloroquine. A retrospective study of the medical records of patients hospitalized with Covid-19 from March to April 2020 and correlated analysis of therapy with Chloroquine/Hydroxychloroquine, Azithromycin, Oseltamivir and corticosteroids was performed. A total of 122 patients were evaluated, with a high percentage of patients admitted to the ICU (41.8%). The main symptoms were: dyspnea (68.9%), fever (84.4%) and cough (81%). Total mortality was 11.5% (N=14), with a mean age of 73 years (var 55-87). Patients discharged from the hospital had a mean age of 49.7 years. A high report of comorbidities associated with hospital admission was detected, mainly SAH, DM, cardiological and neuropsychiatric diseases. The use of the medications chloroquine or hydroxychloroquine had no impact on mortality (p=0.55), nor was the use of azithromycin (p=0.78) or corticosteroids (p=0.3). Patients who required ICU admission had lower mean hemoglobin levels compared to admission, as well as increased inflammatory markers (leukocytes, platelets, D-dimers, TGO, CRP and LDH). It was concluded that the use of chloroquine/hydroxychloroquine was ineffective in terms of mortality.